(untitled) (Medical Forum Monthly, 2024)
Objective: Determine the frequency of response with eltrombopag in persistent immune thrombocytopenia. Design of Study: Descriptive case series study Place and Duration of Study: This study was conducted at the Department of Hematology, Shaikh Zayed Hospital Lahore from September, 2014 to March, 2015. Materials and Methods: A total of 40 cases of immune thrombocytopenia were included. Socio-demographic data like name, age and sex was taken. Patients were given eltrombopag (25mg/day) for 3 weeks. Platelet count was noted at day 7, day 14 and day 21 of treatment. These tests were performed on hematology analyzer Sysmex XT1800i. Other variables like partial response and no response were also noted. Results: Male patients were 23 (57.5%) while female patients were 17 (42.5%) with mean age was 32.97±12.13 years. The mean platelet count was calculated as 109.12+11.29 x109/l. The complete response with eltrombopag in persistent immune thrombocytopenia in 34 (85%) while 6 (15%) had partial response and no cases was recorded with no response. Conclusion: The frequency of response with eltrombopag in persistent immune thrombocytopenia is goods in our population and in future we can use this drug for the management of immune thrombocytopenia.